Kelompok gaya belajar reflektor menurut teori Honey Mumford dalam paradigma perpustakaan - Zakirman Zakirman (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
School paradigm today is not only about transmite of information, but how to change the habit of learning process being active and autonomous. Many theoris of learning process in education context was develop, such as: behaviorisme learning theory, cognitivisme learning theory, constructivisme and humanisme learning theory. If we look educational concept in social context, teacher and all learning environment use humanisme as learning theory. For this adherent, learning process must refer to human/individualistic. Honey Mumford devide students by learning process as four group, are: activist, theorist, pragmatist and reflector. Reflector is one of Honey Mumford theory and ussually the students with this type have carefully to get a conclusion and need many information to support their concept. A research show if reflector is the dominant group to visit the library every time. Based on this research, the organizer of library must understand about their habit and know their necessity to learn.